Study of ternary association of anti-microbial drug 1, 10-phenanthroline and Î± - amino acid with copper salt, an ultrasonic investigation of competitive interaction - Kumar Sahoo, Ashok; Kumar Pradhan, Sunil; Kumar Patnaik, Ajaya; Das, Smrutiprava (International Journal of Advanced Chemistry, 2020)
Molecular interaction studies using ultrasonic technique and spectroscopic investigation in ternary liquid mixture of drug 1,10-Phenanthroline, an Î±- amino acid Glycine and a transition metal salt like CuCl2 in aqueous medium has been carried out at 300.15K and 2 MHz frequency. Using experimental values of density (Ï),ultrasonic velocity (U) and UV analysis, different acoustical parameters such as adiabatic compressibility (Î²),intermolecular free length (Lf), acoustic impedance (z),relative association (RA),apparent molar volume (Vâˆ…), apparent molar adiabatic compressibility (Kâˆ…) are evaluated for the mixture of drug, glycine and inorganic salt CuCl2 at various concentrations. The ultrasonic and spectroscopic investigation clearly shows coordinative association of drug as a ligand with transition metal salt. Further interaction of glycine as an Î±- amino acid indicates a competitive association in the ternary system. The outcomes were expressed in terms of molecular interactions and the variation in parameters under varying solute concentrations providing conclusive remarks regarding the strength of intermolecular interactions in the ternary system with a bio-physical novelty.Â